PEDAGOGICAL AND PSYCHOLOGICAL FACTORS OF ADJUSTING STUDENTS' MOTIVATION TO SAFE LIFE IN INCLUSIVE EDUCATION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article highlights the possibilities of purposeful and effective use of motivational factors in the organization of the process of inclusive education, its pedagogical and psychological mechanisms, as well as aspects related to the safety of life of students, and proposes a model.